72 Exploring the influence of a medical leadership and management intercalation on students'views and attitudes at a single uk medical school. (31st October 2017) - Khan, Saad Mahmud; Court, Jessica
Abstract : Aims: The 2010 Medical Leadership Competency Framework outlines ways in which leadership can be incorporated into the undergraduate curriculum. The General Medical Council's "Tomorrow's Doctors" highlights how medical leadership and management (MLM) teaching is essential for medical students. Consequently, the Birmingham Medical Leadership Society (BMLS), a student-led society at the University of Birmingham, advocated for and helped set up the Healthcare Management and Leadership (HML) intercalated degree. Our study aimed to determine whether this intercalation has changed its student's views towards their career ambitions and their attitude towards the importance of MLM as a necessary skill for future doctors. Methods: We created and distributed questionnaires to the current student cohort (n=10). These questionnaires asked students about basic demographic information and required them to mark on a Likert scale in response to questions about their attitudes to MLM and their career ambitions. Results: The average percentage increase in perceived MLM knowledge after completing semester 1 was 199.07%. Moreover, all students thought that MLM training for medical students was more important after completing Semester 1, with an average percentage increase of 73.44%. Apart from one student who was equally motivated to become involved in MLM later in their career, all other students reported being more motivated after joining the HML intercalation, with an average percentage increase of 95.46%. Lastly, all students were of a stronger opinion that MLM was a necessary skill for future doctors after starting the intercalation. Conclusion: The results show that the intercalation was successful in positively influencing students' attitudes and views about MLM. Moreover, our results indicate that medical schools should look to include MLM teaching on the curriculum, and engage students in this process to ensure opportunities for further development are not missed.